Price Transmission in Iranian Wholesale-retail Meat Market: Implications for Market Power - Omrani, Mohammad; Tash, Mohammad Nabi Shahiki; Akbari, Ahmad (International Journal of Economics and Financial Issues, 2017)
Asymmetric price transmission affects the welfare of producers and consumers leading to a decrease in the efficiency of the market system through increasing the marketing margin. That is why the analysis of the price transmission is of great importance. The current study aims to investigate simultaneously the market power of meat suppliers in retail market through a mixed model and the price transmission trend between wholesale and retail meat markets using a two-regime model. For this purpose, quarterly data for the period 1994-2013 were used. Results indicated that the exercise of market power is possible for retail suppliers through charging higher prices only for a short period in a year and such an insignificant market power induces a welfare effect of as low as 0.34%. Moreover, in the second regime with higher probability, a price increase in the wholesale level is transmitted to the retail level with a higher coefficient in a long term, which is important in terms of policy making. On the other hand, an asymmetric price transmission was observed in a medium term, short term and long term and it was found that the asymmetry is not the same in two regimes. According to the probability of regimes, there can be more severe price transmission from wholesale level to retail level in most cases. Keywords: price transmission, market power, meat production JEL Classifications: C52, C32, Q13